Effect of sodium silicate solution on total chlorine of crude palm oil under biphasic conditions - Hari, Zulfa Kurnia Umani; Syamsul Bahari, Abdullah; Saidatul Shima, Jamari; Che Rahmat, Che Mat; Mohd Sabri, Mahmud (AIP Publishing, 2025)
Chlorine is a feedstock to toxic formation in palm cooking oil. Removing it using dilute alkaline at palm oil mills prevents its reactive contact with hydrolyzed oil to produce monochloride propanediol and glycidyl esters while minimizing saponification. Sodium silicate (SS) can particularly buffer sodium hydroxide presence in an aqueous phase. Therefore, this study aimed to characterize SS solution and test its dechlorination effect on crude palm oil (CPO) in a few series of mixing. FTIR was used to delineate functional groups of crude palm oil before and after the mixing. Hydroxide ion concentrations and total chlorine content were similarly determined from pH meter reading and by using combustion ion chromatography, respectively, in oil and aqueous phases. Hydroxide ion dissociation from the SS solution followed limiting, intermediate-step models. Chlorine content rapidly decreased less than 10 min with the addition of the SS solution to below 1 ppm, which was high than 97% conversion. However, the aqueous phase might pose emulsion problem due to formation of soap at the volume ratio of CPO:SS below higher than 2.33 and mole ratio of SiO2:Na2O higher than 1.